How innovative organization culture affects firm performance in the wake of enterprise resource planning? evidence from energy- and non-energy-sector firms in Pakistan - Ashraf, Yumna; Ali, Fahad (Frontiers in Environmental Science, 2022)
Rapid globalization during the last few decades has caused many difficulties for firms to survive, sustain, and maximize shareholders’ wealth. The Enterprise Resource Planning (ERP) system provides extensive access to data and upgraded information to achieve the specified objectives. This study examines how Innovative Organizational Culture (IOC) affects firm performance in Pakistan. In doing so, this study collects a comprehensive dataset from 234 high- and medium-level managers working in different sectors across six major cities of Pakistan. We construct several hypotheses and employ Partial Least Squares Structural Equation modeling to test the selected premises. The results reveal that IOC and the benefits of ERP are positively related to firm performance, IOC is also positively associated with the implementation of ERP, and the implementation of ERP is positively related to the benefits of ERP. Regarding mediating relationship among the constructs, this study shows that the implementation of ERP mediates the relationship between IOC and the benefits of ERP, and the benefits of ERP mediate the relationship between the implementation of ERP and firm performance. Given that Pakistan has been facing a chronic energy crisis for the last few decades, this study conducts a subsample analysis and divides the sample into two groups – “energy and manufacturing” and “service and non-manufacturing” sector firms. Our robustness tests reveal that the implementation of ERP is positively and significantly related to firm performance only in the subsample of service and non-manufacturing sector firms. In contrast, it is negatively and insignificantly related to firm performance in the subsample of energy and manufacturing sector firms. The findings of this study provide numerous operational insights to managers to adequately emphasize and strengthen IOC to sustain the change management system. Specifically, this study suggests that senior- and medium-level managers should continuously monitor the implementation of ERP and determinedly engage themselves in the team management and communication process to achieve higher firm performance.